2018
DOI: 10.21767/2248-9215.100077
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sowing Dates on Varying Maize (Zea mays I.) Varieties Grown under Agro-Climatic Condition of Peshawar, Pakistan

Abstract: The rapid climate changes are imperative to evaluate and find ways that suite to maize-specific varieties either hybrids or varieties with appropriate sowing dates to avoid the critical growth stages from the stresses due to climate condition. Sowing at proper time and selection of good verity are the most important factor cropping system. A field experiment was conducted at the University of Agriculture Research Farm during summer 2016 to evaluate the influence of sowing dates on varying maize varieties grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 7 publications
(8 reference statements)
3
12
0
Order By: Relevance
“…Biological biomass includes the total biomass of the above ground plant parts of the crop. After threshing grains were collected and corn grain yield was measured (Ali et al, 2018). The ratio of grain yield to biological yield is expressed as harvest index (Cao et al, 2016).…”
Section: Observations and Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Biological biomass includes the total biomass of the above ground plant parts of the crop. After threshing grains were collected and corn grain yield was measured (Ali et al, 2018). The ratio of grain yield to biological yield is expressed as harvest index (Cao et al, 2016).…”
Section: Observations and Data Collectionmentioning
confidence: 99%
“…Annual production of 6900 thousand tones adds 2.6% value addition in agriculture and 0.5% in country GDP (Rehman et al, 2020). The yield contributing agronomic traits and grain yield of maize are affected by numerous factors i.e., inappropriate time of sowing (Moosavi et al, 2012), delay sowing (Ali et al, 2018), weeds *Corresponding author: fasihullahhaider281@gmail.com infestation (Haider et al, 2019), utilization of unapproved and non-certified seeds, shortage of water (Golbashy et al, 2010), salts stress and extreme heat stress (Fink, 2017), in particular during the maize reproductive and vegetative phase (Nagar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The means for the 100 grain weight was statistically significant from SD1-SD2 (8.07 g), SD1-SD3 (10.49 g) and SD2-SD3 (2.42 g). The effect of sowing date on maize yield has been studied in Pakistan and results showed that early sowing of maize cultivars gave higher grain yield (Ali et al, 2018). The cob length mean difference between SD1-SD2, SD1-SD3 and SD2-SD3 were 0.21, 0.45 and 0.25 cm, respectively.…”
Section: Treatment Effect Of Sowing Date On 100 Grain Weight Grain mentioning
confidence: 99%
“…Additionally, the selection of specific maize cultivars has implication on the management of the SD. Maize growth and yield is influenced by changes in temperature (10 -30°C) and rainfall, and this is associated with sowing date (Ali et al, 2018;NSW, 2009). It requires 450 -600 mm of water per season and this is acquired from the root soil water reserves (du Plessis, 2003).…”
Section: Introductionmentioning
confidence: 99%